Ecoliteracy Sampah Pembalut Sekali Pakai pada Santri Pondok Pesantren Annuqayah Guluk-Guluk Sumenep - Halim, Abdul; Nabilla, Dila Fitri; Paisun, Paisun; Hasanah, Lutfi Uswatun (Universitas Nurul Jadid, 2024)
The modern community's alarming waste issue is single-use sanitary pads. Every day, 26 tons of sanitary pad waste are generated in Indonesia. Over a year, each person is estimated to produce 300 sanitary pad wastes, totaling around 11,000 wastes throughout their lifetime. In Islamic boarding schools (pesantren), this sanitary pad waste problem also needs immediate attention. At Annuqayah Islamic Boarding School, with a total of 3,468 female students, there is a potential of producing 1,040,400 single-use sanitary pad wastes annually. Hence, reducing sanitary pad waste is crucial. This community service activity aims to reduce single-use sanitary pad waste through minimizing their usage. The method employed in this activity was through the Participatory Action Research (PAR) approach, where students were encouraged to be more environmentally conscious and gradually abandon the use of single-use sanitary pads. The strategies involved in the activity include conducting Focus Group Discussions (FGD), Environmental Film Discussions, Environmental Seminars, training on making environmentally friendly sanitary pads, establishing an environmentally friendly sanitary pad production house, FGDs on policy formulation regarding the implementation of environmentally friendly sanitary pads, and mentoring on the implementation of environmentally friendly sanitary pads in the pesantren. The results of the community service show that this activity successfully increased students' awareness and concern for the environment, enhanced students' knowledge about single-use sanitary pads, provided life skills training on making environmentally friendly sanitary pads, established regulations prohibiting the use of single-use sanitary pads in the pesantren, and implemented the use of environmentally friendly sanitary pads at Annuqayah Islamic Boarding School